APPLICATION OF GENERATIVE AI TO AUTOMATE ANALYTICAL REPORTS: OPPORTUNITIES, RISKS, AND QUALITY CONTROL METHODS (American Journal of Pedagogical and Educational Research, 2025)
The article discusses modern approaches to the use of generative models (LLM ) for automating the preparation of analytical reports: architectures (including retrieval-augmented Generation ), practical benefits and economic effects, key risks (hallucinations , distortions , data leakage, compliance), as well as quality control and verification methods (technical and organizational). Practical recommendations for implementing generative AI in business analytics are offered.